(untitled) (Scientific journal of the Fergana State University, 2023)
In the 20-30s of the XX century, new forces appeared in the Uzbek stage art, capable of developing this sphere. In order to develop this field of art, the intelligentsia sent talented young men and women to study in Moscow and Baku. Based on memoirs and archival sources, the article describes the difficulties and achievements of Halima Nasyrova in the process of studying in Baku, later awarded the high title of People’s Artist